Design of hierarchy extractor for very large scale integration (VLSI) integrated circuit design - Hidayat, Randy Williams. (2009)
Nowadays, electronic manufacturing technology has been developed tremendously and it allows the creation of monolithic integrated circuits that involve millions of transistors. Therefore, in view of the increasing complexity of VLSI Circuits, there is a need for sophisticated computer-aided design (CAD) tools to automate the synthesis and verification steps in the design of VLSI systems.